Moderate Islam As The Civilizational Middle Path: A critical reading of kh. Said Aqil Siradj’s Islamic Discourse - M. Hadi Sutiyo; Khimmataliev Dustnazar Omonovich (Al-Ittishol: Jurnal Komunikasi dan Penyiaran Islam, 2026)
This study aims to examine the concept of moderate Islam as a middle path of civilization through a critical reading of the Islamic discourse of KH. Said Aqil Siradj. In his perspective, moderate Islam is not merely understood as a compromising attitude or a neutral position between two opposing extremes, but rather as an Islamic paradigm rooted in the tradition of Ahlussunnah wal Jama’ah and oriented toward humanity, nationhood, and the sustainability of civilization. This research employs a qualitative approach using critical discourse analysis to examine the texts of thought, sermons, and public statements of KH. Said Aqil Siradj that are relevant to issues of Islamic moderation, diversity, and the relationship between religion and the public sphere.The findings indicate that the discourse of moderate Islam constructed by KH. Said Aqil Siradj positions Islam as a moral and cultural force capable of bridging tensions between religious texts and social realities, between Islamic identity and Indonesian national identity, and between tradition and modernity. Moderate Islam is projected as a civilizational middle path that rejects extremism, radicalism, and narrow formalism, without losing the substantive theological values of Islam.This study affirms that moderate Islam, according to KH. Said Aqil Siradj, holds strategic relevance in fostering social harmony, strengthening national cohesion, and responding to contemporary civilizational challenges. These findings are expected to enrich scholarly discussions on moderate Islamic thought and to contribute conceptually to the development of the discourse of Islam rahmatan lil ‘alamin in Indonesia.